Friday

April 18, 2014

April 18, 2014

Posted by **Tomika** on Wednesday, June 13, 2007 at 3:42pm.

1. x^2-6x-3=0

2. 2x^2+10x+11=0

Step 1.

Move the constant to the other side.

X^2 -6x + ?? = 3 + ??

To find ??, take 1/2 the x term and square it, then add it to both sides; therefore, 1/2*6 = 3 and 3^2 = 9.

X^2 -6x + 9 = 3 + 9

X^2 -6x + 9 = 12.

(X+3)^2 = 12

X+3 = sq rt 12

Solve for X. Post your work if you get stuck. The other one is worked the same way.

**Related Questions**

math,correction,plz - Solve each of the following quadratic equations by ...

Math - Can someone please check my answers below for accurateness? The ...

(: - help with Quadratic Equations and Functions: 5)Solve 2x2 +6x = 4 by ...

algebra - do I do this correct and if not can you please show and tell me what I...

math - solve each of the following equations by completing the square and show ...

Math - How would I solve the quadratic equation: 2x^2 + 6x = 0 I would factor ...

Math 3 - If you want to be eligible for partial credit, please show your work. ...

math - solve the following system of equations algebraically or graphically for ...

math? - 5)Solve 2x2 +6x = 4 by completing the square. 6)Solve 3x2 - 6x- 24 = 0 ...

Help With Math - Using the quadratic formula to solve equations. -12^2 + 12 x-9...